2023
DOI: 10.1002/advs.202205058
|View full text |Cite
|
Sign up to set email alerts
|

Oral Fungal Alterations in Patients with COVID‐19 and Recovered Patients

Abstract: The oral bacteriome, gut bacteriome, and gut mycobiome are associated with coronavirus disease 2019 (COVID‐19). However, the oral fungal microbiota in COVID‐19 remains unclear. This article aims to characterize the oral mycobiome in COVID‐19 and recovered patients. Tongue coating specimens of 71 COVID‐19 patients, 36 suspected cases (SCs), 22 recovered COVID‐19 patients, 36 SCs who recovered, and 132 controls from Henan are collected and analyzed using internal transcribed spacer sequencing. The richness of or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 40 publications
0
1
0
Order By: Relevance
“…The oral microbiome is the second largest and most diverse microecosystem of up to approximately 1000 microbial species, which is crucial in maintaining oral as well as systemic health ( Deo and Deshmukh, 2019 ). Emerging studies have shown that oral microbiota is associated with various diseases ( Hayes et al., 2018 ; Radaic and Kapila, 2021 ; Hu et al., 2023 ; Lacunza et al., 2023 ), and can be used as a diagnostic tool for specific diseases or cancer, such as rheumatoid arthritis ( Zhang et al., 2015 ) and pancreatic cancer ( Vogtmann et al., 2020 ). Our previous research has verified the functional significance of the human tongue microbiota in COVID-19 ( Ren et al., 2021 ) and SLE ( Guo et al., 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…The oral microbiome is the second largest and most diverse microecosystem of up to approximately 1000 microbial species, which is crucial in maintaining oral as well as systemic health ( Deo and Deshmukh, 2019 ). Emerging studies have shown that oral microbiota is associated with various diseases ( Hayes et al., 2018 ; Radaic and Kapila, 2021 ; Hu et al., 2023 ; Lacunza et al., 2023 ), and can be used as a diagnostic tool for specific diseases or cancer, such as rheumatoid arthritis ( Zhang et al., 2015 ) and pancreatic cancer ( Vogtmann et al., 2020 ). Our previous research has verified the functional significance of the human tongue microbiota in COVID-19 ( Ren et al., 2021 ) and SLE ( Guo et al., 2023 ).…”
Section: Introductionmentioning
confidence: 99%